Clinically Significant Statin-Drug Interactions in Older Patients with Chronic Diseases - Alyahawi A. A.; Measar M; Alwesabi M; Alkaf A (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Background: People over 55 are more likely to have chronic conditions and be treated with multiple drug combinations. This can lead to drug-drug interactions (DDIs), which are often not considered in clinical practice. Statins are useful for older patients who have or are at risk for cardiovascular disease (CVD), need to be taken regularly over a long period of time, and may experience DDI. The risk of DDI varies between different statins, and the incidence and severity of statin interactions in elderly patients taking concomitant medications are significant. Objectives: The present study evaluate the prevalence and severity of clinically significant statin side effects among elderly patients (aged 55 years and older) receiving statin therapy for 18 months after discharge from a hospital in Sana’a; from January 2021 to June 2022. Methods: This retrospective cross-sectional study was carried out from January 2021 to June 2022 at a private hospital in Sana’a City, Yemen. Data collection was obtained from electronic medical register (covering demographic, clinical, and drug-therapy-related variables). The format was also filled with; BP, Sr.cr, HbA1c, HR, Total cholesterol, TG, LDL, HDL, AST, and ALT values for each patient. Drug interactions were identified using both Medscape and Lexicomp software. Results: Out of 200 patients, there were 175 (87.5%) individuals had a total of 865 clinically significant drug-drug interactions. specifically speaking, 55 (27.5%) individuals had a total of 72 clinically significant statin-drug interactions. 57 (79.1%) of which were category C, 14 (19.44%) of which were category D, and only 1 (1.39%) category X statin-drug interaction. There was also an association between advanced age, co-morbidities, and concomitant drugs with the presence of statin-drug interaction. The majority of atorvastatin medication interactions may be avoided by adhering to best practices in clinical care and clinical pharmacology, such as avoiding complicated treatment regimens, utilizing a single pharmacy for all prescriptions, and recognizing patient risk factors. Conclusion: From this study, it can be concluded that statins have a significant effect in the elderly, depending on many different factors as the use of many medications. Class C statin-drug interactions were also noted to be the most common, followed by category D statin-drug interactions.